ANALYSIS OF THE INCIDENCE OF DIARRHEA IN TODDLERS 0-59 MONTHS IN COMMUNITY HEALTH CENTERS - Rika Afriyani; Lilis Suryani; Ali Harokan (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Diarrhea is one of the major health problems in children under five in many countries. Diarrhea can cause dehydration, impaired growth, and even death in children under five if not treated appropriately. Puskesmas areas are often the center of public health services, and understanding the incidence of diarrhea in children under five in these areas is important for developing effective prevention and control strategies. The research design is crossectional which aims to analyze the incidence of diarrhea in toddlers 0-59 months. Independent variables in this study are parental education, nutritional status, hand washing habits before feeding, exclusive breastfeeding, clean water sources, and family latrines. While the dependent variable is the incidence of diarrhea. The sampling technique was proportional random sampling. Proportional random sampling. Sample calculation using the lemeshow formula obtained a total of 90 with an anticipated dropout of 10% so that the sample involved in this study was 99. The analysis used was univariate, bivariate, and multivariate. The results of the study reported that there was a relationship between parental education, nutritional status, hand washing habits, exclusive breastfeeding, clean water sources, and latrines on the incidence of diarrhea in toddlers 0-59 months in the Jayapura Health Center Area, East Ogan Komering Ulu Regency in 2024. The most dominant variable associated is the family latrine variable. This research is recommended to further strengthen the role of posyandu and the role of cadres as a form of community mobilization so that the ODF village declaration so that PHBS runs and the incidence of diarrhea in toddlers can be overcome